ANALISIS PENINGKATAN KEPUASAN MAHASISWA TERHADAP TEACHING TEAM MATA KULIAH DEPARTEMEN MANAJEMEN TEKNOLOGI ITS - Noer, Lissa Rosdiana (2477 - 6165, 2017)
Improving students’ satisfaction to the teaching subjects team of Department of Technology Management ITS Department was assessed using Gap Analysis. The analysis was chosen to find out the expectation and reality that students served to academic service provided by teaching team. Industrial Management, Project Management, and Information Technology Management. Total subjects were 23 pursued by studnt of 2nd, 3rd, and 4th semester. The data processing results show that there were 17 subjects with valid data. Enhancements needed to improve students’ satisfaction are by implementating midterm exam, final exam, and task (presentation) on schedule, giving lecture material according to the expertises, giving clear and understandable lecture material, giving subjects literature, performing objective and transparent assessment, explaining lesson plan, holding lecture on schedule, being able to understand students’ characteristic, being available for discussion outside the class meetings, accepting criticism and suggestion. Keywords: Teaching Team, Student Satisfaction, Analysis Gap.